Heteromeric channels formed by TRPC1, TRPC4 and TRPC5 define hippocampal synaptic transmission and working memory - Bröker-Lai, Jenny; Kollewe, Astrid; Schindeldecker, Barbara; Pohle, Jörg; Nguyen Chi, Vivan; Mathar, Ilka; Guzman, Raul; Schwarz, Yvonne; Lai, Chung Lun Alan; Weißgerber, Petra; Schwegler, Herbert; Dietrich, Alexander; et al. (The EMBO journal, 2017)
Canonical transient receptor potential (TRPC) channels influence various neuronal functions. Using quantitative high‐resolution mass spectrometry, we demonstrate that TRPC1, TRPC4, and TRPC5 assemble into heteromultimers with each other, but not with other TRP family members in the mouse brain and hippocampus. In hippocampal neurons from Trpc1/Trpc4/Trpc5‐triple‐knockout (Trpc1/4/5−/−) mice, lacking any TRPC1‐, TRPC4‐, or TRPC5‐containing channels, action potential‐triggered excitatory postsynaptic currents (EPSCs) were significantly reduced, whereas frequency, amplitude, and kinetics of quantal miniature EPSC signaling remained unchanged. Likewise, evoked postsynaptic responses in hippocampal slice recordings and transient potentiation after tetanic stimulation were decreased. In vivo, Trpc1/4/5−/− mice displayed impaired cross‐frequency coupling in hippocampal networks and deficits in spatial working memory, while spatial reference memory was unaltered. Trpc1/4/5−/− animals also exhibited deficiencies in adapting to a new challenge in a relearning task. Our results indicate the contribution of heteromultimeric channels from TRPC1, TRPC4, and TRPC5 subunits to the regulation of mechanisms underlying spatial working memory and flexible relearning by facilitating proper synaptic transmission in hippocampal neurons.